Black Female Masculinity in Toni Morrison's Sula - Hameed Mankhi, Azhar (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This paper portrays female masculinity and the position of black women in Toni Morrison's Sula (1973). Women in this novel reconstruct their selfhood through rebelling on social norms and traditions. In their resistance, they act more like men than women. They work to create their selfhood and identity through rejection of the conventional gender roles, which women play in the community. Morrison's women contradict the stereotypes of black women in African American fiction. This paper records the fortunes of black women in different matriarchal environments inside black society. .